SCREENING FITOKIMIA DAN AKTIVITAS ANTIRADIKAL BEBAS EKSTRAK METANOL DAUN GAHARU (Gyrinops versteegii) - I Made Mega; Dewa Ayu Swastini (Jurnal Kimia (Journal of Chemistry), 2010)
It has been done screening fitokimia and the determination of free antiradical activity extract methanol ofgaharu leaf. The screening fitokimia determined by the colour test and free antiradical activity determined bydiphenyl pykril hydrazil (DPPH) method according to sphectrophotometry UV-Vis, before that the honey was dilutedwith methanol and then the absorbance was measured on 497nm, 517 nm, and 537 nm. The result showed thatmethanol extract of gaharu leaf contain phenol, flavonoid and terpenoid compound and the free antiradical activityshowed inhibitor percent is 106,32 % (5”) and 111,31 % (60’).